2022
DOI: 10.12681/jhvms.29373
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and antimicrobial resistance of vancomycin resistant Enterococcus spp. (VRE) and methicillin-resistant S. aureus (MRSA) on beef and chicken meat, and workers hands from slaughterhouses and retail shops in Turkey

Abstract: The objectives of this study were to determine the presence and antimicrobial resistance of Methicillin Resistant Staphylococcus aureus (MRSA) and Vancomycin Resistant Enterococci (VRE) on beef and chicken carcasses and meat, and workers hands’ at processing time from a cattle and a poultry slaughterhouse, and beef and chicken meat at retail level. Disk diffusion method was used to determine the antimicrobial resistance profile of the Enterococcus spp. and S. aureus isolates. Minimum Inhibitory Concentration (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
3
0
0
Order By: Relevance
“…In this study, E. hirae was the predominantly isolated species, which accounted for 37.7% of total Enterococcus isolates, and the remaining 33.3%, 15.5%, 12.2%, and 1.1% of the isolates were identified as E. casseliflavus, E. faecium, E. faecalis, and E. gallinarum, respectively (Table 1). Wide variation (0-90.6%) in the prevalence of Enterococci in food-producing animals has been reported in different countries [1,4,5,12,16,[31][32][33]. In the present study, the speciation of the isolates confirmed that E. hirae was the most prevalent species identified from sheep and goat carcass samples.…”
Section: Discussionsupporting
confidence: 71%
“…In this study, E. hirae was the predominantly isolated species, which accounted for 37.7% of total Enterococcus isolates, and the remaining 33.3%, 15.5%, 12.2%, and 1.1% of the isolates were identified as E. casseliflavus, E. faecium, E. faecalis, and E. gallinarum, respectively (Table 1). Wide variation (0-90.6%) in the prevalence of Enterococci in food-producing animals has been reported in different countries [1,4,5,12,16,[31][32][33]. In the present study, the speciation of the isolates confirmed that E. hirae was the most prevalent species identified from sheep and goat carcass samples.…”
Section: Discussionsupporting
confidence: 71%
“…In this study, E. hirae was the predominantly isolated species, which accounted for 37.7% of total Enterococcus isolates, and the remaining 33.3%, 15.5%, 12.2%, and 1.1% of the isolates were identified as E. casseliflavus, E. faecium, E. faecalis, and E. gallinarum, respectively (Table 3). Wide variation (0-90.6%) in the prevalence of Enterococci in food-producing animals has been reported in different countries [1,4,5,12,16,[31][32][33]. In the present study, the speciation of the isolates confirmed that E. hirae was the most prevalent species identified from sheep and goat carcass samples.…”
Section: Discussionsupporting
confidence: 71%
“…This research is particularly relevant because of the high consumption of meat by a significant portion of the local population. Wide variation (0–90.6%) in the prevalence of enterococci in food-producing animals has been reported in this study and different countries 1 , 4 , 5 , 12 , 16 , 35 37 . In the present study, the speciation of the isolates confirmed that E. hirae was the most prevalent species identified from sheep and goat carcass samples.…”
Section: Discussionsupporting
confidence: 54%